2010
DOI: 10.1007/s11270-010-0498-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Substrates in Wetland Soils on Denitrification

Abstract: Different substrates were evaluated to investigate their effect on nitrate removal and denitrifying bacterial community in soils obtained from wetland. Serial batch kinetic tests were conducted on soils obtained from wetland mixed with glucose and sawdust using KNO 3 solution. Column tests were also conducted on soils obtained from wetland mixed with three different substrates (glucose, sawdust, and scoria coated with zero-valent iron) using KNO 3 solution. For the batch tests, the nitrate removal efficiency f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It was reported previously that C is the limiting factor for bacterial growth in most soils (Aldén et al ., ; Demoling et al ., ). To avoid any bias which may be introduced by addition of C (Goldfarb et al ., ; Hien et al ., ), we did not add any C source to the soil cores. Thus, it is reasonable to see such a result.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that C is the limiting factor for bacterial growth in most soils (Aldén et al ., ; Demoling et al ., ). To avoid any bias which may be introduced by addition of C (Goldfarb et al ., ; Hien et al ., ), we did not add any C source to the soil cores. Thus, it is reasonable to see such a result.…”
Section: Discussionmentioning
confidence: 99%
“…Lina Feng et al [8] found that temperature affects the growth state of microorganisms such as Ulva prolifera and that the structure of enzymes is destroyed and their activity inhibited at excessively high temperatures. Saleema Saleh-Lakha et al [9] found that temperature does not inhibit the transcription of denitrification genes but has different effects on the expression of denitrification genes, and temperature has a significant effect on enzyme activity. Temperature is also the most important factor affecting the growth and reproduction of microorganisms [10,11].…”
Section: Introductionmentioning
confidence: 99%